2016
DOI: 10.3892/ol.2016.4675
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 protein expression in a murine model of osteosarcoma

Abstract: Osteosarcoma is an aggressive type of bone tumor that commonly occurs in pediatric age groups. The complete molecular mechanisms behind osteosarcoma formation and progression require elucidation. B7-H3 is a protein of the B7 family that acts as a co-stimulatory molecule with a significant role in adaptive immune responses. The link between B7-H3 expression and its role in different types of cancer remains unclear. B7-H3 protein exhibits different functional roles in in vivo and in vitro conditions that remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Our previous study revealed that the cancer tissue from hepatocellular carcinoma (HCC) patients exhibited significantly increased levels of B7-H3 (10). B7-H3 has also been reported to be involved in the development of a variety of other solid tumor tissue cancer types, including osteosarcoma, pancreatic cancer, glioma, bladder cancer and non-small cell lung cancer (11)(12)(13)(14)(15), as well as in the development of inflammatory diseases (16).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that the cancer tissue from hepatocellular carcinoma (HCC) patients exhibited significantly increased levels of B7-H3 (10). B7-H3 has also been reported to be involved in the development of a variety of other solid tumor tissue cancer types, including osteosarcoma, pancreatic cancer, glioma, bladder cancer and non-small cell lung cancer (11)(12)(13)(14)(15), as well as in the development of inflammatory diseases (16).…”
Section: Introductionmentioning
confidence: 99%
“…B7-H3 expression was elevated in osteosarcomas of human and mice and was found to be associated with tumor aggressiveness and metastasis. 20,22 Dong and Ma 21 demonstrated via IHC that B7-H4 expression in osteosarcoma was elevated and correlated with an advanced tumor stage and distant metastasis. In addition, a high expression of B7-H4 protein was an independent poor prognostic factor for overall survival time.…”
Section: Gradementioning
confidence: 99%
“…[16][17][18][19] Recent studies have revealed that the protein expression of B7-H3 and B7-H4 is elevated in sarcoma and assists in tumor progression. [20][21][22] Nonetheless, limited information has been available regarding the expression of B7-H3 and B7-H4 within PTs.…”
Section: Introductionmentioning
confidence: 99%